Value Stream Mapping: Literature Review and Implications for Service Industry - Indra Setiawan; Tumanggor, Ojakma Sihar Panaili; Hardi Purba, Humiras (Jurnal Sistem Teknik Industri, 2021)
Value Stream Mapping (VSM) is a technique used in the lean principle that helps analyze the flow of materials and information needed to bring a product or service to the customer. VSM has received a lot of attention in the industrial sector from both the manufacturing industry and the service industry. The development of VSM tools has grown rapidly. Much of the research using VSM tools is carried out in industry and universities. This literature review aims to provide an overview of the implementation of Value Stream Mapping in the service industry and to find out its implications. This paper involves a review study of 45 papers related to a case study of VSM implementation in the service industry. The study was conducted using the Google Scholar database, Researchgate, ProQuest, Elsevier. This paper provides an advantage for the service industry to find problems related to waiting times. This paper extends the knowledge and study of the application of VSM as an unexplored tool in several branches of industry. VSM can also serve as a complementary approach, capable of increasing outcomes in many areas other than services. This paper also provides benefits for future researchers to add insights and references for studies related to VSM in the service industry sector.